Lifestyle of Teenagers Hanging Out at Bagasta Cafe (Descriptive Study of Napa Village, Batang Torung District, South Tapanuli) - Ahmad Akhir Hasibuan (Journal of Sumatera Sociological Indicators, 2023)
In this modern era, hanging out in cafes has become a common habit among teenagers, including those in Napa Village, Batang Toru District. Cafes have become a part of the community's life in the village, with many teenagers always hanging out in cafes. This research is a descriptive study with a qualitative approach, using data collection techniques such as observation, interviews, and documentation. The informants in this study were 13 teenagers who consider cafes as their lifestyle. The results of this study show that cafes are now a solution for the needs of the community, especially for teenagers. They no longer feel satisfied with enjoying the living room or family lounge just to chat or discuss. Cafes are considered to provide more comfort and satisfaction, both physically and mentally, to fulfill their desires. The behavior of teenagers in Napa Village is categorized as a way of using money, goods, places, and time. The habit of hanging out in cafes is seen as a need to fill their free time for personal pleasure and as a way to show their social identity. In addition, the free time given by parents to their teenage children can influence them to become spendthrift, lazy, and prioritize playing in cafes instead of studying at home. The existence of Bagasta Cafe is seen as a place for hanging out that can show their existence and elevate their social status.